Edukasi Hukum Positif dan Hukum Islam tentang Pernikahan Tanpa Perceraian Sah bagi Masyarakat Desa Laut Biru, Kecamatan Kabila Bone - Kasim, Nur Mohamad; Samon, Siti Nurfadilla; Fauzan, Ahmad; Husaeri (Madani: Jurnal Pengabdian Ilmiah, 2025)
This community service program aims to enhance the legal understanding and awareness of the people in Laut Biru Village, Kabila Bone District, regarding the importance of marriage registration and lawful divorce procedures based on positive law and Islamic law. The implementation methods included lectures, group discussions, case simulations, and legal consultations involving religious leaders, village officials, and the general public. The results indicate a significant increase in participants' knowledge about the necessity of marriage registration, lawful divorce procedures, and the protection of women's and children's rights. Prior to the program, most community members believed that physical separation was sufficient to end a marriage; however, after the educational sessions, their understanding shifted to appreciate the importance of formal legal processes. The involvement of religious leaders and village officials also strengthened the local legal advocacy network. Although there are still challenges such as administrative and cultural barriers, the participatory and collaborative approach has proven effective in fostering a sustainable legal awareness culture. This community service experience is expected to serve as a model for other villages in developing a law-abiding, just, and dignified society in accordance with positive law and Islamic principles.